Design of PNIPAAM covalently grafted on halloysite nanotubes as a support for metal-based catalysts. Issue 60 (8th June 2016) - Massaro, M.; Schembri, V.; Campisciano, V.; Cavallaro, G.; Lazzara, G.; Milioto, S.; Noto, R.; Parisi, F.; Riela, S.
Abstract : A thermo-responsive polymer (PNIPAAM) was covalently grafted on the external surface of halloysite nanotubes and used as support for palladium nanoparticles for application as catalyst in Suzuki cross coupling in water under microwave irradiation. Abstract : A thermo-responsive polymer such as poly( N -isopropylacrylamide) (PNIPAAM) was covalently grafted on the external surface of halloysite nanotubes (HNTs) by means of microwave irradiation. This nanomaterial was used as a support and stabilizer for palladium nanoparticles. The obtained HNT–PNIPAAM/PdNPs was characterized by means of TGA, SEM, EDS and TEM analyses. The palladium content of the catalyst was estimated to be 0.4 wt%. The stability of the catalytic material at different temperatures (below and above the PNIPAAM lower critical solution temperature) was tested in the Suzuki reaction under microwave irradiation. In addition, TEM analysis after five consecutive runs was performed. The catalyst showed a good catalytic activity toward the Suzuki cross-coupling reaction between phenylboronic acid and several aryl halides in aqueous media under microwave irradiation and low palladium loading (0.016 mol%, 8 μg of Pd). Turnover numbers (TONs) and frequencies (TOFs) up to 6250 and 37 500 h −1, respectively, were reached. The catalyst was easily separated from the reaction mixture by centrifugation and reused for five consecutive cycles with a small drop in its catalytic activity.